2022
DOI: 10.3390/chemosensors10060221
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Detection Methods

Abstract: A fast and highly specific detection of COVID-19 infections is essential in managing the virus dissemination networks. The most relevant technologies developed for SARS-CoV-2 detection, along with their advantages and limitations, will be presented and fully explored. Additionally, some of the newest and emerging COVID-19 diagnosis tools, such as biosensing platforms, will also be introduced. Considering the extreme relevance that all these technologies assume in pandemic control, it is of the utmost relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…The RT-LAMP and RT-HDA developed in our study have a multiplex format, which reduces the risk of false negatives because even if a mutation occurs in one target gene the second target gene can still be detected. Additionally, the sensitivity of RT-HDA and RT-LAMP is higher and has been estimated 100% for both methods in our study, whereas the reported sensitivity of antigen tests is 56.2% with 27.9% of false negatives [ 7 ]. Table 6 presents a summary of LFA-based tests analyzed by Zhang et al [ 2 ].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The RT-LAMP and RT-HDA developed in our study have a multiplex format, which reduces the risk of false negatives because even if a mutation occurs in one target gene the second target gene can still be detected. Additionally, the sensitivity of RT-HDA and RT-LAMP is higher and has been estimated 100% for both methods in our study, whereas the reported sensitivity of antigen tests is 56.2% with 27.9% of false negatives [ 7 ]. Table 6 presents a summary of LFA-based tests analyzed by Zhang et al [ 2 ].…”
Section: Discussionmentioning
confidence: 75%
“…Although they are easy to perform, the tests have major limitations, which have been overcome by LFA combined with nucleic acid amplification tests. For example, the antibody and antigen LFA tests rely on the detection of only one SARS-CoV-2 protein, which may lead to false negatives, especially when some mutations occurs [ 7 ]. The RT-LAMP and RT-HDA developed in our study have a multiplex format, which reduces the risk of false negatives because even if a mutation occurs in one target gene the second target gene can still be detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only one target can be implemented in each assay, thus limiting the accuracy of the test. In addition, optimization of primers remains challenging ( Lino et al, 2022 ). CRISPR-based diagnostics enabled the development of multiplexed and portable nucleic acid detection devices based on several Cas enzymes for the identification of human viruses, and was recently approved by the US Food and Drug Administration (FDA) for COVID-19 screening ( Javalkote et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are four potential methods that can be employed to detect SARS-CoV-2, such as RT-LAMP, CRISPR–Cas, biosensors, and sequencing [ 13 ]. The virus concentration found in individuals and, especially, in food is relatively low, requiring prior amplification for detection.…”
Section: Introductionmentioning
confidence: 99%